An Interdisciplinary Approach for Valuing Changes After Ecological Restoration in Marine Cultural Ecosystem Services - Pouso, Sarai; Borja, Ángel; Uyarra, María C. (Frontiers in Marine Science, 2020)
Ecological restoration in marine ecosystems is considered strategic to recover environmental conditions and ecosystem services. However, the traditional single-discipline perspectives followed for analysing the results of both restoration projects (focused in the analysis of biophysical changes) and valuation of ecosystem services (focused in economic valuation), do not provide useful theoretical frameworks when working with cultural ecosystem services, where socio-economic and environmental components are complexly interrelated. We propose an interdisciplinary approach for analysing changes in cultural ecosystem services in restored marine ecosystems, based on the DAPSI(W)R(M) framework and following a social-ecological system approach. Our methodology considers environmental, social and economic elements that may be contributing to changes in the provision and demand for cultural ecosystem services in restored ecosystems. Our approach was tested in the Nerbioi estuary, a system that, after the implementation of a wastewater treatment plant at the end of the 20th Century, changed from being one of the most polluted estuaries in Europe to a nearly recovered system. Based on previous studies that have analysed partial components of the restoration process and of the recreational ecosystem services, here we provide an interdisciplinary picture of the changes occurred in the last 25 years, directly linking the management measures adopted to an increase in human well-being. In the applied methodology, the three discipline domains (social, economic, and environmental) transcend each other to provide a new holistic view, completely different from what one would expect from the addition of the parts. In conclusion, this interdisciplinary approach provides a systematic framework for studying changes in cultural ecosystem services in restored systems, with a practical application for valuing human benefits as outcomes of marine restoration projects.